THEORETICAL ISSUES ON IMPROVING LEXICAL COMPETENCE AS A SIGNIFICANT COMPONENT OF COMMUNICATIVE COMPETENCE (Ustozlar uchun, 2024)
Annotation: this article discusses the current issues on improving Lexical competence in language teaching process. Lexical competence is quite a new term and not many researches were conducted so far. Author of the article tries to explore it as a crucial part of FLT and gives reliable literature review. Dissertations and research works related to the topic were analyzed.